1963
DOI: 10.1002/1097-4679(196307)19:3<298::aid-jclp2270190311>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviation of the WAIS for clinical use: An attempt at validation

Abstract: PROBLEM I n a recent study, Satz and Mogel@) constructed an abbreviated form of the WAIS in which all scales and subtests were represented. The attempt was to obviate a shortcoming in previous abbreviated forms which used only those combinations of subtests (usually four) that provided maximal correlations with Full Scale IQ(4). Such procedures have limitations, except for research application, by virtue of their emphasis on single I& indices. By representing all scales and subtests in the recent abbreviated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1965
1965
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Educational level was included because of its relationship to socioeconomic level and general intelligence (Griffith & Taylor, 1960b). The three test variables were the Abbreviation of the WAIS for Clinical Use (Mogel & Satz, 1963;Satz & Mogel, 1962), the Trail Making Test (TMT) (Armitage, 1946;Reitan, 1958), and the MFDT (Graham & Kendall,I960),4 Only the Performance IQ Scale of the Abbreviated WAIS was administered; this was to insure a nonverbal psychometric IQ control for the BRT. Pearson ;• correlations between the Abbreviated and original WAIS forms have been reported as follows (Satz & Mogel, 1962): Verbal IQ = .99; Performance IQ = .97; Full Scale IQ = .99.…”
Section: Additional Test and Nontest Variablesmentioning
confidence: 99%
“…Educational level was included because of its relationship to socioeconomic level and general intelligence (Griffith & Taylor, 1960b). The three test variables were the Abbreviation of the WAIS for Clinical Use (Mogel & Satz, 1963;Satz & Mogel, 1962), the Trail Making Test (TMT) (Armitage, 1946;Reitan, 1958), and the MFDT (Graham & Kendall,I960),4 Only the Performance IQ Scale of the Abbreviated WAIS was administered; this was to insure a nonverbal psychometric IQ control for the BRT. Pearson ;• correlations between the Abbreviated and original WAIS forms have been reported as follows (Satz & Mogel, 1962): Verbal IQ = .99; Performance IQ = .97; Full Scale IQ = .99.…”
Section: Additional Test and Nontest Variablesmentioning
confidence: 99%
“…Not only does this make it unclear how an individual's performance would be altered by administering only those items scored on the short form, but it also leaves unclear the logistics of such an administration. Mogel and Satz (1963) recognized and addressed the assumption of expected performance on short forms in their publication of a study that used a test-retest method to compare full administration with short form administration of the WAIS. In the discussion of their results, they report similar predictive power of the Satz-Mogel (1962) short form whether rescored from a full administration or administered independently.…”
Section: Discussionmentioning
confidence: 99%
“…In the discussion of their results, they report similar predictive power of the Satz-Mogel (1962) short form whether rescored from a full administration or administered independently. However, they fail to describe the independent short form administration procedures (Mogel & Satz, 1963). Therefore, the clinical use of selected-item short forms remains questionable.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of 50 sentences of increasing difficulty in vocabulary and comprehension. I n terms of its accuracy, a previous study (2) reported substantial correlation between the OLT and other tests. However, these results were attenuated by correlations performed using several intelligence tests, based on 85 Ss.…”
mentioning
confidence: 96%